2012
DOI: 10.1002/jmri.23857
|View full text |Cite
|
Sign up to set email alerts
|

Regional values of diffusional kurtosis estimates in the healthy brain

Abstract: PurposeTo provide estimates of the diffusional kurtosis in the healthy brain in anatomically defined areas and list these along previously reported values in pathologies.Materials and MethodsThirty-six volunteers (mean age = 33.1 years; range, 19–64 years) underwent diffusional kurtosis imaging. Mean kurtosis (MK), radial kurtosis (RK), mean diffusivity (MD), radial diffusivity (RD), and fractional anisotropy (FA) were determined in 26 anatomical structures. Parameter estimates were assessed regarding age depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 27 publications
(63 reference statements)
1
61
2
1
Order By: Relevance
“…The voxel-based analysis (VBA) and ROI results finding positive correlations of age with MK and RK diverge from previous studies in which negative correlations were found (Coutu et al, 2014;Gong et al, 2014;Latt et al, 2013). Age-related differences in AK were only reported in Coutu et al (2014) and in contrast to our findings showed negative correlation with age.…”
Section: Kurtosis Metrics and Ndi May Reveal Signs Of Late Maturationcontrasting
confidence: 86%
See 1 more Smart Citation
“…The voxel-based analysis (VBA) and ROI results finding positive correlations of age with MK and RK diverge from previous studies in which negative correlations were found (Coutu et al, 2014;Gong et al, 2014;Latt et al, 2013). Age-related differences in AK were only reported in Coutu et al (2014) and in contrast to our findings showed negative correlation with age.…”
Section: Kurtosis Metrics and Ndi May Reveal Signs Of Late Maturationcontrasting
confidence: 86%
“…To date, only a few studies have applied this technique to study differences across the life span. In these studies, mean kurtosis (MK), a measure of tissue complexity, was found to increase in WM during maturation and decrease in healthy aging (Coutu et al, 2014;Falangola et al, 2008;Gong et al, 2014;Latt et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This finding might be related to an initial inflammatory process in which high cellularity could restrict overall diffusion, with the diffusion distribution becoming more non-Gaussian and the MK increasing. Recently, Lätt et al 15 provided estimates of DKI for various cerebral regions in healthy brains and compared them with DTI parameters. They found a strong positive correlation between MK and FA in WM (r ϭ 0.81, P Ͻ 10 Ϫ5 ) and a strong negative correlation between RK and RD (r ϭ Ϫ0.95, P Ͻ 10 Ϫ5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is expected that RK will decrease when diffusion becomes less restricted during demyelination. Lätt et al 15 recently estimated and compared the regional DKI values of healthy brain tissues with DKI values obtained from previous studies of different pathologies. In another study in which DKI was applied after stroke onset, 16 higher MK values were observed in ischemic WM, which eventually progressed to gliosis, compared with ischemic WM that maintained a normal appearance.…”
mentioning
confidence: 99%
“…2018; 15(3):e56115. 7 structure and morphology changes due to cerebral white matter density and capacity increase in the early teens and maturity while it gradually reduces after old age (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%